PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA SMK - Umi Ibrahim (PEDAGOGIK, 2022)
Ability to communicate properly and affectively both orally and in writing become very important forvocational high school. The study aims to improve students writing descriptive skill through Project BasedLearning at one of vocational high school in central Halmahera. Descriptive quantitative were applied inthis study. There are 20 students participated in this study. Data were collected through pre-test and posttest.Data were analyzed to see whether the students writing skill increase after joining Project Basedlearning model in learning to write descriptive text. The findings show that after using Project BasedLearning Model can improve students’ ability writing descriptive text. It is suggested that students shouldwork collaborative and share with their friends in writing. Teacher can use project based Learning modelin teaching writing. Due to this model can allow students can work collaboratively and sharing with friendlearning to write which is enable students to increase their skill.